The impact of contraceptives on the vaginal microbiome in the non-pregnant state - Bakus, Cassandra; Budge, Kelly L.; Feigenblum, Nicole; Figueroa, Melissa; Francis, Antonia P. (Frontiers in Microbiomes, 2023)
The vaginal microbiome exists in a dynamic state and its disruption, by diminution of Lactobacillus concentrations, can induce a state of microbial imbalance with significant health consequences, such as increased risk of STI acquisition, preterm labor, and low birth weight babies. This delicate balance of microbes can be affected by many processes such as mechanical practices (ie. douching) and hormonal changes: physiologic (ie. menstrual cycle, menopause, puberty), pathologic (ie. PCOS) and exogenous (ie. contraceptives). Contraceptives fall into mechanical and hormonal categories, both of which prevent unintended pregnancy. The mechanical contraceptives of spermicides, diaphragms, and cervical caps alter the vaginal ecosystem, with spermicides being linked to an increased risk of vaginal dysbiosis. The impacts of Copper T intrauterine devices (Cu-IUDs) and hormonal contraceptives on the vaginal microbiome are contradictory. A better understanding and consensus of how contraceptive methods affect the vaginal microbiome is needed.